2015
DOI: 10.5194/hessd-12-4471-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability in snow cover phenology in China from 1952 to 2010

Abstract: Abstract. Daily snow observation data from 672 stations, particularly the 352 stations with over ten annual mean snow cover days (SCD), during 1952–2010 in China, are used in this study. We first examine spatiotemporal variations and trends of SCD, snow cover onset date (SCOD), and snow cover end date (SCED). We then investigate SCD relationships with number of days with temperature below 0 °C (TBZD), mean air temperature (MAT), and Arctic Oscillation (AO) index, the latter two being constrained to the snow se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Based on the daily snow observation data from meteorological stations, Ke et al . examined the variability of snow cover phenology in China during 1952–2010 17 . They found that snow cover significantly started later and melted earlier with the increasing temperature, but SCD did not show significant trend within this time span.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the daily snow observation data from meteorological stations, Ke et al . examined the variability of snow cover phenology in China during 1952–2010 17 . They found that snow cover significantly started later and melted earlier with the increasing temperature, but SCD did not show significant trend within this time span.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies mainly focused on changes in the extent, duration and depth of snow cover 26 , 27 , while spatial and temporal patterns of snow cover start (SCS) and melt (SCM) dates of the TP have not been well understood. Studies have systematically analyzed the variability of snow cover phenology in China 17 and the Northern Hemisphere 12 , using meteorological stations. However, these stations distribute unevenly and predominantly located in low-altitude areas of the TP.…”
Section: Introductionmentioning
confidence: 99%
“…The 1-cm SD threshold was adopted under a wide range of snow conditions in previous studies [52], [53]. Moreover, Ke et al [54] indicated that a shallow snow cover (SD < 1 cm) can reduce the data reliability in snow-related studies in China. Therefore, we defined SD ≥ 1 cm as snow and as snow-free otherwise.…”
Section: Validation Methodology 1) Validation Based On the Cloud Amentioning
confidence: 99%
“…China covers a vast area and a variety of climate regions, and its snow-covered regions are widely distributed geographically with evident spatial differences (Tan et al, 2019). Northern Xinjiang, Northeastern China-Inner Mongolia (hereafter referred to as Northeast China) and the Tibetan Plateau are the three main regions with stable snow cover in China (Ke et al, 2016;Fig. 1a).…”
Section: Introductionmentioning
confidence: 99%